Probing Differential Binding Mechanisms of Phenylalanine-Glycine-Rich Nucleoporins by Single-Molecule FRET - Tan, Piau Siong (Methods Enzymol, 2018)
Phenylalanine-glycine-rich nucleoporins (FG-Nups) are intrinsically disordered proteins, constituting the selective barrier of the nuclear pore complex. They are highly dynamic under physiological conditions and studying their interaction with nuclear transport receptors (NTRs) is key to understanding the molecular mechanism of nucleocytoplasmic transport. Distinct conformational features of FG-Nups interacting with diverse NTRs can be detected by multiparameter single-molecule fluorescence energy transfer (smFRET), which is a powerful technique for studying the dynamics and interactions of biomolecules in solution. Here we provide a detailed protocol utilizing smFRET to reveal differential binding mechanisms of FG-Nups to NTRs, with a focus on practical considerations on sample preparation of unglycosylated and glycosylated FG-Nups, site-specific dual-labeling, smFRET measurements, and data analysis.